A business plan for the startup of iMind preschool in Selangor, Malaysia - Gan, Chin Ho (2024)
The goal of the business plan for the iMind Institution, written as a graduation project, is to open a ground-breaking early childhood educational facility in Serenia City, Malaysia. The plan, which targets families with monthly incomes between RM5,000 and RM10,000, is based on thorough market analysis, financial forecasting, and strategic marketing. In the analysis of Malaysia's ECCE market's regulatory and competitive environment, iMind stood out for using the Reggio Emilia method and having excellent infrastructure. To guide targeted investments, a SWOT analysis identifies the major opportunities and challenges. To increase reach and engagement, the marketing strategy uses a 7Ps framework that combines traditional and digital tactics. Excellent educational experiences are prioritized in operational plans through a structured curriculum and teacher preparation. Additionally described are potential exit strategies for stakeholders as well as long-term growth opportunities. With a strong emphasis on quality and scalability, the plan portrays iMind as a promising competitor in Serenia City's early childhood education market.